PERTUMBUHAN STEK BIBIT KOPI DENGAN PERBEDAAN JUMLAH RUAS PADA MEDIA TANAH-KOMPOS - Retno Muningsih; Lu’lu’ul Fitria Ashari Putri; Renan Subantoro (MEDIAGRO, 2018)
The purpose of this study was to determine the growth response of various segments of coffee cuttings in the soil-compost planting media. This research was conducted from January 2018 to April 2018 at the Green House Polytechnic LPP Yogyakarta with BP 288 coffee plant clones. The treatment used was one segment cuttings, two sections cuttings, three sections cuttings and four sections cuttings with variable number of leafes, leaf color, shoot stem diameter, shoot length and number of shoots. This research method uses a non-factorial Randomized Complete Block Design (RCBD) with further DMRT methods.Based on the results of the study, it was found that soil-compost showed C-organic content of 8.54%, N content of 0.23%, P content of 0.14% and K content of 0.21% and the best results of plant growth were on the cuttings treatment of one segment cuttings, two sections cuttings, three sections cuttings and unfavorable growth, namely in the treatment of cuttings four sections.Keyworsd: Coffee, Cuttings, Growth